INSTRUCIONISMO E CONSTRUCIONISMO COMO FERRAMENTA NA CONSTRUÇÃO DO CONHECIMENTO MATEMÁTICO - Fonseca Coelho, Bruno; Aparecida Gomes Afonso, Gisele; Carla Sabino Cunha, Josiana; da Silva Viana, Luciene (LINKSCIENCEPLACE, 2026)
This article deals with the construction of knowledge from constructionist and instructionalist methods as a tool for mathematical education, evidencing the practice of the learning process and the student 's autonomy, thus exploring the same as an active agent related to the dialogue theme. In this paper he presents experiences in the application of software such as Geogebra and Photomath, to observe the interaction of the students in the reports from construccionist and instructionalist methods in the midst of the capacity of student development in the learning process.